2014
DOI: 10.4161/epi.32252
|View full text |Cite
|
Sign up to set email alerts
|

A pilot examination of the genome-wide DNA methylation signatures of subjects entering and exiting short-term alcohol dependence treatment programs

Abstract: Alcoholism has a profound impact on millions of people throughout the world. However, the ability to determine if a patient needs treatment is hindered by reliance on self-reporting and the clinician’s capability to monitor the patient’s response to treatment is challenged by the lack of reliable biomarkers. Using a genome-wide approach, we have previously shown that chronic alcohol use is associated with methylation changes in DNA from human cell lines. In this pilot study, we now examine DNA methylation in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
79
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 39 publications
9
79
3
Order By: Relevance
“…While the former [54] found no significant differences pre-vs-post treatment, the latter [55] observed a general increase in methylation with alcohol consumption over a 12-year period, particularly in CKM, PHOX2A, and NPDC1. With regard to wider biological pathways, EWAS studies indicated that the most common pathways that were hypermethylated in response to alcohol use were those related to G-protein mediated and GTPase signal transduction processes [51,54,55], whereas pathways associated with stimulus and stress responses, as well as immune and inflammatory processes, where likely to be hypomethylated [51]. Hypomethylation was also observed in long terminal repeat (LTR) regions of retrotransposons in the superior frontal cortex of postmortem alcohol users [56].…”
Section: Adulthoodmentioning
confidence: 93%
See 3 more Smart Citations
“…While the former [54] found no significant differences pre-vs-post treatment, the latter [55] observed a general increase in methylation with alcohol consumption over a 12-year period, particularly in CKM, PHOX2A, and NPDC1. With regard to wider biological pathways, EWAS studies indicated that the most common pathways that were hypermethylated in response to alcohol use were those related to G-protein mediated and GTPase signal transduction processes [51,54,55], whereas pathways associated with stimulus and stress responses, as well as immune and inflammatory processes, where likely to be hypomethylated [51]. Hypomethylation was also observed in long terminal repeat (LTR) regions of retrotransposons in the superior frontal cortex of postmortem alcohol users [56].…”
Section: Adulthoodmentioning
confidence: 93%
“…Hypomethylation was also observed in long terminal repeat (LTR) regions of retrotransposons in the superior frontal cortex of postmortem alcohol users [56]. Other important pathways related to apoptosis [52,54,55], metabolism [53], as well as GABA and dopamine systems [40,53].…”
Section: Adulthoodmentioning
confidence: 98%
See 2 more Smart Citations
“…The epigenetically differentially regulated regions included hyper-as well as hypo-methylated genes in patients. [32][33][34] The most recent study by Clark et al identified CNTN4 as a risk factor for alcohol use by examining the methylation status of approximately 27 million autosomal CpG sites and comparing them to GWAS data. 35 Earlier candidate-gene based studies investigating the influence of therapeutic interventions on DNA methylation reported decreasing homocysteine levels in alcohol dependent patients during alcohol treatment, 20,21,36,37 leading to the hypothesis that DNA methylation levels also decrease during alcohol treatment.…”
Section: Introductionmentioning
confidence: 99%